ACCEPTANCE OF BUILDING INFORMATION MODELLING-VIRTUAL REALITY (BIM–VR) IN SELANGOR CONSTRUCTION INDUSTRY - Peniel Ang Soon Ern, Peniel Ang Soon Ern; Abdul Halim, Nurhana Jannah; Tsai Kai Len, Tsai Kai Len; Kasim, Narimah; Tuan Ismail, Tuan Noor Hasanah (2024)
The integration of Building Information Modelling and Virtual Reality (BIM-VR) technology allows users to experience BIM model and view BIM data such as cost and material type in real-time in an immersive visualisation system. However, the future applicability and practicality of BIM-VR integration has yet to be established in Malaysia's construction industry. Hence, the aim of this paper is to study the acceptance of BIM-VR amongst the Selangor design consultant and the objectives are to identify the awareness and involvement of Malaysian design consultants in BIM-VR in Selangor and to determine the challenges of BIM-VR implementation in the Selangor construction industry. This research adopted a quantitative approach by conducting questionnaire survey with architects from different companies located in Selangor. The data obtained from 33 respondents were analysed by using Statistical Package for Social Science (SPSS) where the test conducted were frequency analysis, descriptive analysis, and Pearson correlation. The findings revealed that most respondents are aware of BIM and VR adoption in the architecture firm. However, the lack of BIM-VR implementation was due to training and software cost and a lack of exposure to BIM-VR technology among other construction players. In conclusion, the respondents are aware and willing to involve actively in this integrated technology whilst seeing the need to collectively overcome the challenges BIM-VR. Government push and support in this area will be a catalyst in BIM-VR update and hence will contribute significantly to the efficiency of design and construction process.